Indigenous nationals, Canadian citizens : from first contact to Canada 150 and beyond - Courchene, Thomas J., 1940- (Queen's policy studies., 2018)
"Indigenous Nationals/Canadian Citizens begins with a detailed policy history from first contact to the Sesquicentennial with major emphasis on the evolution of Canadian policy initiatives relating to Indigenous peoples. This is followed by a focus on the key Supreme Court decisions that have dramatically enhanced Indigenous peoples' legal and constitutional rights. Attention is then directed to the Truth and Reconciliation Commission and the associated 'Calls to Action, ' including their relationship to the United Nations Declaration on the Rights of Indigenous Peoples."--